Analysis of the impact of foreign debt, inflation rate and poverty rate on Indonesia’s economic growth - Nainggolan, Elisabeth; Widyawati, Retno Febriyastuti; Fenny, Fenny (Junal Ilmu Manajemen, 2025)
The purpose of this study is to analyze variables that influence Indonesia's economic growth from 1994 to 2023. The variables believed to impact economic growth in this research are foreign debt, inflation rate, and poverty rate. This research is quantitative, utilizing multiple linear regression analysis with time series data over a period of 30 years. All data used in this study were sourced from the World Bank, Bank Indonesia, and the Badan Pusat Statistik. The results of the partial analysis show that foreign debt, inflation rate, and poverty level each have a significant effect on economic growth. Specifically, foreign debt, inflation, and poverty have a negative impact on economic growth. Additionally, the three independent variables, such as foreign debt, inflation rate, and poverty rate that simultaneously have a significant effect on Indonesia's economic growth.